1995
DOI: 10.1021/bi00040a002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a methylammonium-binding site on methylamine dehydrogenase of Thiobacillus versutus

Abstract: The nonconvertible substrate analogues di-, tri-, and tetramethylammonium are bound with fairly high affinity to oxidized methylamine dehydrogenase (MADHox) from Thiobacillus versutus and induce the same red-shift in the optical absorbance spectrum of MADHox as do the monovalent cations Cs+, Rb+, and NH4+. Like the monovalent cations, trimethylamine also competitively inhibits the reduction of MADHox by methylamine. Rapid-scan experiments show that within the first few milliseconds of the reaction between MADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…It must be noted that for MADH from Thiobacillus ersutus, resonance Raman spectroscopy studies [10] indicated that the influence of NH % + was due to its proximity to TTQ and not covalent modification. Addition of NH % + to T. ersutus MADH caused a red shift of the absorption maximum of its UV-visible spectrum from 440 nm to 453 nm, which is similar to the change caused by addition of Cs + [19]. AADH and MADH are similar in that the spectral changes induced by NH % + \NH $ are different from those induced by metallic cations.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…It must be noted that for MADH from Thiobacillus ersutus, resonance Raman spectroscopy studies [10] indicated that the influence of NH % + was due to its proximity to TTQ and not covalent modification. Addition of NH % + to T. ersutus MADH caused a red shift of the absorption maximum of its UV-visible spectrum from 440 nm to 453 nm, which is similar to the change caused by addition of Cs + [19]. AADH and MADH are similar in that the spectral changes induced by NH % + \NH $ are different from those induced by metallic cations.…”
Section: Methodsmentioning
confidence: 67%
“…It has been shown for MADH that univalent cations affect the stability of the TTQ semiquinone [19]. Recent studies show that univalent cations enhance the rate of the proton-transfer reaction that gates the electron-transfer reaction from the substratereduced aminoquinol TTQ of MADH to amicyanin (G. R.…”
Section: Significancementioning
confidence: 99%
“…The later study demonstrates a primary kinetic isotope effect of approximately 9 -17 (at 30°C), considerably higher than the semiclassical limit for proton abstraction (16). This binding site has the same affinity and the specificity as the type I site of the oxidized MADH (23,24). We postulate that the water molecule may be replaced by the cation that may partially occupy the proximal position.…”
Section: Discussionmentioning
confidence: 85%
“…The type I cations act as competitive inhibitors of MADH reduction by substrate (22,23). A transient, red-shifted intermediate is also observed in the absorption spectrum of MADH prior to its reduction by methylamine (23). From these results, the binding site for these monovalent cations was predicted to be located at the active site in the vicinity of the cofactor atom O-6 and to mimic the first step of the reaction.…”
mentioning
confidence: 90%
See 1 more Smart Citation